The implementation of blockchain technologies. The impact on the shadow economy for a sustainable future - Mititelu, Roxana - Adriana; Amzuică, Bogdan Florian (Technium Social Sciences Journal, 2023)
The study has addressed a major research gap existing in the implementation of block chain technologies in public administration. The paper has further focused on the impact of blockchain implementation on the shadow economy, for a sustainable future. Based on the defined research problem, the study objective entailed establishing the effect of blockchain adoption and implementation on the shadow economy, for a sustainable future. Thus, the research question went as follows: the effect the effect of block chain adoption and implementation on the shadow economy, for a sustainable future? The study went for a mixture of primary and secondary data. The study participants and data points entailed stakeholders and players in the cryptocurrency world, drawn from public administration. The data was coded and inputted in SPSS 2. This was followed with reliability test, descriptive statistics and a series of regression analysis. The regression analyses were run to test the hypothesis formulated from the conceptual framework.